Coastal Subsistence Strategies and Mangrove Swamp Evolution at Bubog I Rockshelter (Ilin Island, Mindoro, Philippines) from the Late Pleistocene to the mid-Holocene. (2nd October 2019) - Boulanger, Clara; Ingicco, Thomas; Piper, Philip J.; Amano, Noel; Grouard, Sandrine; Ono, Rintaro; Hawkins, Stuart; Pawlik, Alfred F.
Abstract: Subsistence adaptations to coastal environments and the capacity to take advantage of mangrove swamps has likely played an important role in the success of the maritime colonization of Southeast Asian and Wallacean islands by modern humans. Yet, ichthyoarchaeological studies remain rare in this part of the world. Bubog I rockshelter (Ilin Island, southwestern Mindoro, the Philippines) has yielded a stratigraphic filling extending from 30 ka to 4 ka, including a human-produced shell midden. Several remains from marine and terrestrial animals have been recovered from the site. We report here on an Australo-Melanesian subsistence behavior based on ichthyofaunal, crustacean, and large mammal remains. Their adaptation to successfully exploit different marine environments from open reef to mangrove swamps is demonstrated by the continuous presence of fishes from these marine zones throughout the stratigraphy and by the development of a range of fishing and foraging techniques. The increased hunting of Sus oliveri furthermore shows increased foraging in tropical rainforests after 6 ka. Interestingly, based on crustaceans analysis, mangrove foraging in Bubog I declined when the development of these swamps was at their maximum in other islands in the Philippines. Variability in subsistence strategies therefore appears to be a response to changing landscapes during the Pleistocene–Holocene transition with a strong marine specialization that only increased as mangrove habitats declined.